Greek hoards the Cimmerian Bosporus - Abramzon, Michail Grigorʹevič 1961-; Kuznecov, Vladimir Dmitrievič 1953- (Peeters, 2021)
The eleventh volume of 'Coin Hoards' is dedicated solely to hoards of Greek coins found in the Cimmerian Bosporus. The inventory contains records of 271 new hoards or re-evaluations of old ones, and provides an indispensable supplement to the 'Inventory of Greek Coin Hoards' and previous volumes of 'Coin Hoards'. The volume includes many hitherto unrecorded hoards from the early 5th century BC to the 6th century AD. The majority of them were recently acquired by museums in Simferopol, Kerch, Tman, Phanagoria, Temryuk, Anapa, Krasnodar, Novorossiysk, Moscow and St Petersburg from the archaeological missions which had conducted wide-scale excavations in the Krasnodar region and the eastern Crimea. Among the significant recent finds are large hoards of Late Archaic silver coins and Late Bosporan staters from Phanagoria, as well as a group of purses from Mithradates VI's residence there, burnt in 63 BC; a Myrmicium hoard of Cyzicenes; big hoards of Bosporan gold staters from the Taman Peninsula; huge hoards of 3rd-century BC bronze coins (more than 21000 pieces) and coins of the Mithradatic period (15000 and 8000 coins) from the Asiatic Bosporus; and a group of hoards from Mithradates III's fortress in Parosta, a small Bosporan city, which met its end during the Roman-Bosporan War of AD 45-49, etc. Nine notes are devoted to brief publication of a group of the most significant new hoards, related mostly to Phanagoria and the Asiatic Bosporus. Huge Phanagorian hoards of the early 1st century BC are of special interest, containing coins of Euboea, Delos and Crete, the Pontus, western and southern Anatolia and the adjacent islands. The volume is accompanied by 311 plates.
Keywords: Geschichte 500 v. Chr.-600; Münzfund; Münze; Straße von Kertsch; Griechenland -- Altertum